Hydrobiological studies within the tea gardens at Srimangal, Bangladesh. IV. Desmids (17 genera) (Bangladesh Journal of Plant Taxonomy, 2005)
Fifty nine taxa of desmids under 17 genera, namely Cylindrocystis, Netrium, Spirotaenia, Gonatozygon, Penium Closterium, Pleurotaenium, Triploceras, Triplastrum, Hyalotheca, Groenbladia, Bambusina, Teilingia, Sphaerozosma, Spondylosium, Onychonema and Desmidium have been recorded from different aquatic habitats located within the tea gardens at Srimangal, Maulvi Bazar. Eight taxa are described as new records for Bangladesh including two genera, namely, Cylindrocystis and Spirotaenia. Key words Desmids, acidic habitats, phytoplankton, new records DOI: 10.3329/bjpt.v12i2.602 Bangladesh J. Plant Taxon. 12(2): 49-62, 2005 (December)